Completion of FCVRP using Hybrid Particle Swarm Optimization Algorithm - Muhammad Ali; Baiq Nurul Izzah Farida (Jurnal Teknik Industri, 2021)
The issue of green logistics has received full attention from the government and business people. It is closely related to the increase in Green House Gas (GHG) by transportation activities in the logistics sector. Controlling fuel consumption in transportation activities is fundamental in dealing with GHG. Therefore, the Fuel Consumption Vehicle Routing Problem (FCVRP) is proposed as a solution model in optimizing fuel consumption in the logistics sector. This study aims to develop a Hybrid Particle Swarm Optimization (HPSO) algorithm to solve the FCVRP problem. The proposed algorithm is the development of the PSO algorithm with local procedures search. Several experiments were carried out to determine the HPSO parameter's effect on minimizing fuel consumption in the FCVRP. The experiment results show that increasing the population and iteration parameters can produce minimum fuel consumption. Furthermore, the smaller the total fuel consumption produced when the kilometers per liter (KPL) high.